An algorithm for soil identification according to the World Reference Base for Soil Resources - Hasanova, Samira (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
This paper addresses soil identification according to the World Reference Base for Soil Resources. A structure of the database of soil parameters of diagnostic horizons is proposed. Three variants of allocating soils to Reference Soil Groups based only on soil parameters, or on the combination of diagnostic horizons and soil parameters, or only on diagnostic horizons are considered